Drought and herbivory as modulators of intraspecific differentiation in seedlings of a mountain tree - Marcora, Paula Inés (2023)
In mountain ecosystems, plant regeneration might be constrained by multiple factors that change along elevation gradients and promote traits differentiation. Drought is a strong filter for seedling establishment that might be modified by herbivory co-occurrence. Populations of the tree Maytenus boaria support lower soil moisture and higher herbivory pressure at low elevations than at mid-elevations in Córdoba Mountains, central Argentina. Consequently, we expect that populations from the low elevation perform better in response to drought than populations from mid-elevations and that herbivory modifies these responses. Seedlings from the two elevation origins were exposed to two levels of simulated drought and herbivory in a greenhouse experiment. The selected elevations corresponded to the lowest edge of species distribution (with driest soils and highest herbivory pressure) and the central mid-elevation. Performance-related variables, biomass allocation patterns and several morphological and physiological traits were measured. Mortality patterns and most of morphological and physiological variables showed that drought is a stressful factor at the regeneration stage of M. boaria. The drought effect was increased by simulated herbivory in some variables (LMF, RM:SM and SPAD). In most variables, origin did not influence seedling performance, suggesting that drought response of seedlings is independent of populations’ elevation. Only leaf number and water potential were in line with our predictions and showed an origin response to drought.